Diseño de procedimiento para determinar costos de calidad del procesamiento de mortadela en el taller de cárnicos de la UDIV-carrera Agroindustrias- ESPAM MFL - Holguín Zambrano, María José (2015)
The research was conducted in the workshop of meat of the Academic Unit, Links and Research of the ESPAM MFL where products are made as the mortadella, which was the subject of study to design a procedure to determine quality costs that fall in the process, with the purpose of obtaining information about the prices of each input and identify problems in the processing of elaboration of mortadella to know that quality costs affect the final product. To characterize the object of study tools are used as an observation form and the interview addressed to the responsible of the workshop meat area making UDIV know the level of compliance with the process of Bologna. Through the observation form, direct observation and the check list were verified the application of technical regulations and Good Manufacturing Practices (GMP) in each process activity. The Ishikawa Diagram identified relevant problems including inadequate sterilization of equipment and tools for the development of mortadella, the Pareto diagram determined the quality costs that influence the process. The result obtained in this research contributed to the development of the design procedure for determining quality costs that affect the safety of the final product, establishing measures necessary to eliminate shortcomings encountered in the process in order to assist them in fulfilling quality standards (INEN, BPM)